Ensinando o conceito de campo elétrico a partir do fenômeno do raio - Ortiz, João Paulo Martins Tobaruela (2015)
This dissertation is a report of the development and application of a Potentially Meaningful Teaching Units (PMTU), proposed by Moreira, approaching the concept of electric field for high school level. Aiming to contextualize it, the starting point of PMTU is the lightning phenomenon, which is difficult to reproduce at the school lab, is worked with digital educational objects (DEO) and the students were engaged actively in all activities, showing great motivation to study the phenomenon and learn the concepts involved. The construction of conceptual maps by the students with collaborative ways, also allowed them to interact socially, trying to negotiate meanings. The theoretical basis of PMTU uses mainly the Theory of Meaningful Learning of Ausubel. The results gave evidence of the occurrence of significant learning by students, and the acceptance regarding the strategies used.